Factor Analysis of the Efficiency of Russian Oil and Gas Companies - Borodin, Alex; Mityushina, Irina; Harputlu, Mustafa; Kiseleva, Natalia; Kulikov, Andrey (International Journal of Energy Economics and Policy, 2023)
The purpose of the study is to develop theoretical and methodological foundations for the development of tools for assessing the level of financial and technical efficiency of oil and gas companies and identifying reserves for improving efficiency based on the influence of external and internal factors. The theoretical basis of the research consists of the authors’ works devoted to the problems of assessing financial efficiency, technical efficiency, innovation, market and environmental efficiency of companies. Modeling was carried out on the basis of tools for building DEA models, logistic regression, methods of correlation and regression analysis using the functionality of the software product R. The data of 7 companies with the largest revenue in the oil and gas industry by the end of 2020 and macroeconomic indicators of the financial and economic market of the Russian Federation are also components of the information base of the study. The scientific novelty of the research lies in the development of theoretical provisions and methodological tools for evaluating the effectiveness of companies in effective identification by assessing financial and technical efficiency, developing models of the phenomenon and forecasting the effectiveness of companies in the oil and gas industry.